PERBANDINGAN PERTUMBUHAN RUMPUT LAUT (Kappaphycus alvarezii) YANG DIPELIHARA PADA KEDALAMAN BERBEDA DI PERAIRAN TELUK ROTE - Ndun, Kenny Peter; Linggi, Yulianus; Tobuku, Ridwan (Jurnal Aquatik, 2025)
This study was carried out to analyze the growth differences of K. alvarezii at different depths, to identify the environmental factors that affect the growth of K. alvarezii at these depths, and to determine the best depth that provides optimal growth results for K. alvarezii at the research site. This research was carried out for 45 days which took place in the waters of Rote Bay, Lenaoen Beach. The method used in this study is an experimental method and the experimental design used is Complete Random Design (RAL) with 3 treatments and 3 replicates, P1 = Seaweed cultivation on the surface with a depth of 20 cm, P2 = Seaweed cultivation on the surface with a depth of 60 cm, and P3 = Seaweed cultivation on the surface with a depth of 100 cm. In this study, the test material used was Kappaphycus alvarezii seaweed with an initial weight of 100 grams and using the longline cultivation method. The parameters tested in this study are growth parameters and environmental parameters. The results showed that the depth of cultivation had a significant influence on the absolute growth of K. alvarezii in the waters of Rote Bay where the highest absolute growth was achieved at a depth of 20 cm with a value of 828 g, followed by a depth of 60 cm of 667 g, and a depth of 100 cm of 545 g. Environmental conditions at a depth of 20 cm, including the optimal temperature (29.5°C), Salinity (32.1 ppt), high light intensity (about 28,000 lux), and supportive current velocity (20.5 cm/s), strongly support photosynthesis and metabolism processes, thereby accelerating biomass accumulation. In contrast, at deeper depths, decreased light intensity, lower temperatures, and slower currents inhibit growth rates. Therefore, the selection of the right cultivation depth is crucial to maximize the productivity of K. alvarezii and support the sustainability of cultivation businesses in Rote Bay. Keywords: Kappaphycus alvarezii, seaweed, Rote bay